日本海沿岸におけるカワヤツメ（Lethenteron camtschaticum）の伝統漁 - 荒川, 裕亮; 224; アラカワ, ヒロアキ; 柳井, 清治; 1; ヤナイ, セイジ; 20337009; YANAI, Seiji; ARAKAWA, Hiroaki; 138 (石川県立大学, 2021)
カワヤツメ（Lethenteron camtschaticum）は日本国内で重要な水産資源であるが、その漁獲量は減少している。本研究は、カワヤツメ漁（漁具、漁場、漁期）と漁師が有する地域の生態学的知識（LEK）を体系化することを目的として、日本海沿岸における内水面漁業協同組合へのインタビューを行った。カワヤツメ漁は、川の規模や、地形環境、カワヤツメの生態的行動に応じて発達しており、過去には日本海沿岸の北部から中部にかけて分布していた。漁師たちは、漁場に応じて多様な漁具を使用しており、漁法は主にタイプ 1（定置漁）、タイプ 2（横断構造物での漁獲）、タイプ 3（産卵床での漁獲）の 3 種類に分類された。また漁師の有する知識は、淡水におけるカワヤツメの移動として季節的、月周、日周、環境の違いによる行動パターンに関する生態的知見に関する洞察を提供した。しかし、カワヤツメの漁獲量は現在にかけて 1 ～ 10％に減少し、その漁師の数も漁協内において数名にまで減少していた。今後は、カワヤツメと伝統的な漁業活動を守るために、漁師が有する情報を活用し保全計画や順応的管理を確立していく必要がある。 Arctic lamprey (Lethenteron camtschaticum) constitutes an important fishery in Japan, but the catch has decreased This study interviewed representatives of inland fishery cooperatives (FCs) along the Sea of Japan coast about lamprey fishing methods (gear, grounds, and season) and the fishers' local ecological knowledge (LEK). Lamprey fishing developed on the north and central coasts of the Sea of Japan in accordance with river size, environment, and lamprey behavior. The fishers used a variety of gear depending on the fishing ground The fishing was classified into three types: 1) set-net fishing, 2) catching at artificial barriers, and 3) catching at spawning beds. The fishers' LEK provided insights into the migration behavior of Arctic lamprey in freshwater, including seasonal, lunar, diel, and habitat-related differences. However, the mean catch of Arctic lamprey has decreased to 1-10% of past catches and the number of lamprey fishers has decreased to only a few members in each FC. This information should be used to establish a conservation plan for Arctic lamprey and management of the traditional fishing culture. departmental bulletin paper